Über die Typen von P. Gabriel Strobl aus der Familie Dolichopodidae (Diptera). - Morge, Günter; Negrobov, O. P. (Contributions to Entomology = Beiträge zur Entomologie, 1981)
The types of the species of Dolichopodidae described by P. Gabriel Strobl were examined. As a result, Medetera ruficornis Strobl is discribed and included with its caracteristics in the newest key. The position of Hercostomus quadrifilatus (Strobl) is clarified. Nomenclatural Acts quadrifilatus Strobl, 1899 (Gymnopternus (Hypophyllus)), syn. n. of Hercostomus parvilamellatus (Macquart, 1827) ruficornis Strobl, 1898 (Medetera), Lectotype